Mass Loss and Penetration Depth of Hypervelocity Projectiles - Tianhan Xu; Yanyu Qiu; Jie Li; Yihao Cheng; Wei Chen (Shock and Vibration)
Numerous investigations recorded a dramatic decrease in penetration depth at hypervelocity. The decrease is due to the severe mass loss of the projectile. The mechanics of mass loss are complicated, so the entirely theoretical model is still absent. In this paper, we derive a semitheoretical formula for mass loss by solving the equation of motion of the projectile during penetration. The result shows that the decrease in projectile mass at hypervelocity accords with the power law. Furthermore, we obtain a continuous formula for depth of penetration in the entire velocity domain. The theoretical results agree well with experimental data. The formula for the critical velocity of depth decreasing is also obtained as a by-product of the solving procedure.